Surgical manipulation compromises leukocyte mobilization responses and inflammation after experimental cerebral ischemia in mice - Denes, Adam; PRADILLO, JESUS M.; Drake, Caroline; Buggey, Hannah; Rothwell, Nancy J.; Allan, Stuart M. (Frontiers in Neuroscience, 2014)
Acute brain injury results in peripheral inflammatory changes, although the impact of these processes on neuronal death and neuroinflammation is currently unclear. To facilitate the translation of experimental studies to clinical benefit, it is vital to characterize the mechanisms by which acute brain injury induces peripheral inflammatory changes, and how these are affected by surgical manipulation in experimental models. Here we show that in mice, even mild surgical manipulation of extracranial tissues induced marked granulocyte mobilisation (300%) and systemic induction of cytokines. However, intracranial changes induced by craniotomy, or subsequent induction of focal cerebral ischaemia were required to induce egress of CXCR2-positive granulocytes from the bone marrow. CXCR2 blockade resulted in reduced mobilisation of granulocytes from the bone marrow, caused an unexpected increase in circulating granulocytes, but failed to effect brain injury induced by cerebral ischaemia. We also demonstrate that isoflurane anaesthesia interferes with circulating leukocyte responses, which could contribute to the reported vascular and neuroprotective effects of isoflurane. In addition, no immunosuppression develops in the bone marrow after experimental stroke. Thus, experimental models of cerebral ischaemia are compromised by surgery and anaesthesia in proportion to the severity of surgical stress and overall tissue injury. Understanding the inherent confounding effects of surgical manipulation and development of new models of cerebral ischaemia with minimal surgical intervention could facilitate better understanding of interactions between inflammation and brain injury.